Assessment of sorption kinetics of carbon nanotube‐based composite foams for oil recovery application. Issue 14 (12th December 2018) - Piperopoulos, E.; Calabrese, L.; Mastronardo, E.; Abdul Rahim, S. H.; Proverbio, E.; Milone, C.
ABSTRACT: Sorption kinetics of pollutant oils, such as kerosene, virgin naphtha, crude oil, and pump oil, into porous siloxanic foams filled with carbon nanotubes (CNTs) are investigated. Both, pristine and functionalized, CNTs are used as foam fillers. Among all, the foam filled with pristine CNT shows a poor affinity with water and high sorption rate in light oils, in which it achieves the highest absorption values (7991 mg g −1 after 660 s and 6685 mg g −1 after 420 s, respectively, in virgin naphtha and kerosene). The kinetic data are described by the pseudo‐first order, pseudo‐second order, Elovich and intraparticle diffusion models. Results show that chemisorption processes are rate limiting the sorption step. In fact, pseudo‐second order model better represents the equilibrium isotherm data. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47374. Abstract :